[Group portrait of football team in uniform] - Frank Aston::::::photographer::: (1916)
Group portrait of football team in uniform, with asst. coach C.H. Williams and coach D.W. Schlosser; posing in formation on field; team members identified on back. Photo of same team, seated on steps, was published in the Polytechnic J. (v.12, no.1, June 1917) with caption identifying members. [Post card's emulsion layer is damaged -- flaking off in margins of photo.]